EDUKASI FISIOTERAPI BAD POSTURE PADA SISWA-SISWI DI SMP NEGERI 1 KOTA MALANG: PHYSIOTHERAPY EDUCATION OF BAD POSTURE FOR STUDENTS AT SMP NEGERI 1 KOTA MALANG - Maslichatul Nurul Rosida; Indria Sari Shinta; Safun Rahmanto (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Background: Postural Disorder, or disorders related to body posture, which are increasingly found in children lately. The causes of poor posture are not only from sitting positions but also from sleeping positions and activities that trigger body posture disorders, such as playing gadgets, staring at laptop/computer screens, lifting heavy objects, and the type of school bags. Objectives: The counseling was conducted with the intention of educating students about cases of poor posture, particularly with reference to the definition, types, and causes of posture disorders, as well as prevention strategies and physiotherapy exercises to lessen the number of complaints from students when handling devices or carrying bags. Method: Microsoft PowerPoint was utilized as a teaching tool to educate students about health issues related to poor body posture using several questionnaire questions as a measure of knowledge. In 30 students were given pre- and post-tests in the form of questions to gauge the effectiveness of the teaching. Results: The counseling session went well, and the pupils' understanding increased from 30% to 100% after getting instruction, according to the evaluation. This counseling activity, which was conducted at SMP Negeri 1 Kota Malang, Oro-Oro Dowo, Klojen, helped students learn more about poor posture and how to prevent and manage posture-related physiotherapy exercises like pelvic tilt, bird-dog, and cat-camel. Conclusion: To help students prevent and address poor body posture, counseling sessions have been conducted at SMP Negeri 1 Kota Malang, Oro-Oro Dowo, Klojen, Kota Malang. These sessions include exercises such as pelvic tilts, bird-dogs, and cat-camels that can be performed at home to help improve body posture. The majority of students participating in these exercises stated that they were unaware of what causes poor body posture or how to avoid it.